LEGAL LOOPHOLES BEHIND JASTIP: JURIDICAL ANALYSIS OF POWER ATTORNEY AND RISK OF DOCUMENT DESTRUCTION IN TICKET EXCHANGE FOR SEVENTEEN [RIGHT HERE] WORLD TOUR CONCERT IN JAKARTA - Marshanda Aulia Putri; Ratih Damayanti (IPMHI Law Journal, 2025)
The purpose of this study is to analyze the validity of power of attorney for concert ticket exchanges in accordance with Indonesian civil law provisions. This study fills a gap in legal research by focusing on the validity of power of attorney in the exchange of tickets for the Seventeen [Right Here] World Tour in Jakarta, as well as aspects of personal data protection involved therein. The study applies normative legal research methods. The results of this study reveal that the use of a power of attorney in the ticket exchange process, as utilized by ticket exchange services, falls under the category of a special power of attorney governed by Article 1975 of the Indonesian Civil Code. The format of the power of attorney from the promoter complies with the provisions of Article 1320 of the Civil Code. Conclusion of this study is that Mecimapro acts as the data controller responsible for the entire concert. Promoter is obligated to destroy power of attorney documents that have been used and are no longer relevant to the promoter company, as a form of personal data protection and document archive management. The provisions regarding the destruction process are regulated in Article 44 of the Personal Data Protection Law, whose regulations are further strengthened by Government Regulation No. 87 of 1999 on the Procedures for the Submission and Destruction of Company Documents.